2021
DOI: 10.3390/buildings11100461
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Challenges in the Interactions of Design Teams of Construction Projects: A Bibliometric Study

Abstract: There is no comprehensive understanding of the problems that may impact the performance of the different actors that participate in the design of construction projects. In the absence of clarity about the problems and challenges that may impact the interactions, it is not possible to propose action plans to optimize the performance of the design teams. Therefore, this study proposes to identify the main problems and challenges in the interactions of design teams in building projects. A mixed review method is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Moreover, PMs participate in commissioning and start-up activities to integrate project outcomes into existing systems where TCs add positively to PMs' experiences in a manner that can be transferred to future projects. In line with this, Karna and Junnonen (2017) and Galaz-Delgado et al (2021) stressed that PMs should pay sharp focus in resolving design issues at site through effective participation with their teams. The sixth way that TCs contribute to PS is through stimulating PMs' desire to learning.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, PMs participate in commissioning and start-up activities to integrate project outcomes into existing systems where TCs add positively to PMs' experiences in a manner that can be transferred to future projects. In line with this, Karna and Junnonen (2017) and Galaz-Delgado et al (2021) stressed that PMs should pay sharp focus in resolving design issues at site through effective participation with their teams. The sixth way that TCs contribute to PS is through stimulating PMs' desire to learning.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, the 10 research questions mentioned in the introductory chapter of this article are considered. For this, a 3-step methodological procedure was implemented as shown in Figure 2: (i) Bibliometric analysis as a quantitative method, (ii) Systematic review of literature as a qualitative method, and (iii) Mixed review as a method to integrate the findings found [51][52][53]. In this study, the 10 research questions mentioned in the introductory chapter of this article are considered.…”
Section: Bibliometric Analysis and Systematic Content Reviewmentioning
confidence: 99%
“…The 'Links' column describes the number of connections between keywords (the keyword is addressed in a paper with another term together quantity times the number of 'links'). The 'Total Link Strength' column indicates the weight of these links [26]. For instance, in the case of the 'governance' term, there is a 'number of occurrence equal' to three and 'links' equal to nine.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%